The Usage of Greetings Varieties at Widyatama Campus Environment: A Sociolinguistics Study - Dirgantara, Bany Galvin; Gunawan, Hero (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2024)
This Research discusses the types of greetings, Social Factors, and Social Dimensions in the Widyatama campus environment. This Research used a qualitative descriptive method. In analyzing the data, this Research used the theories about sociolinguistics from Wardaugh. The Research also used the theories about Diglossia from Ferguson, polite greetings from Levinson, Social greetings from Labov, and accommodative greetings from Giles. There are 10 data of Greetings in this research but only 3 data that will show in this research due to the data has already enough and can answer the research question. Greetings have different functions according to each type of Greeting, social factors, and social dimensions. They are to explain the participant's role in the usage of greetings in an academic context, to explain the social factors that influence the usage of greetings, and to show the social dimensions that influence greetings, the findings can divide types of greeting into three, which is polite greeting, social greetings, and accommodative greetings and the social factors and social dimension in each greeting.